Rodzina - Cushman, Karen (New York : Clarion Books, 2003)
A twelve-year-old Polish American girl is boarded onto an orphan train in Chicago with fears about traveling to the West and a life of unpaid slavery.
Includes bibliographical references (p. 214-215).
Keywords: Polish Americans -- Juvenile fiction; Polish Americans -- Fiction; Orphans -- Fiction; Orphan trains -- Fiction; Survival -- Fiction; West (U.S.) -- History -- 19th century -- Fiction